1985
DOI: 10.1002/eji.1830150204
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon‐γ can induce the expression of HLA‐DR and ‐DC on DR‐negative melanoma cells and enhance the expression of HLA‐ABC and tumor‐associated antigens

Abstract: Recombinant interferon-gamma (IFN-gamma) induced the expression of HLA-DR when added to the culture medium of HLA-DR- melanoma cell lines. In addition, IFN-gamma induced the expression of another class II antigen, HLA-DC, on a HLA-DR+ and -DC-melanoma cell line and to a lower level on a -DR- and -DC-melanoma line. IFN-gamma also enhanced the expression of HLA-ABC and beta 2-microglobulin, as well as HLA-DR on DR+ melanoma cells. In contrast, IFN-alpha gave no induction of expression of HLA-DR and DC on two DR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 27 publications
2
37
1
Order By: Relevance
“…Thus, repeated administration of anti-IFN-y antibodies should indicate more clearly the contribution of IFN-y in tumor suppression and rejection. In addition, IFN-y might induce the expression of tumorassociated antigen(s) (43,44) as well as MHC class I antigens, although the precise nature of the C1300 cell antigen is not yet known. Actually, preliminary experiments indicated that augmented CTL activity specific for the C1300 cell line was induced in the mice immunized with the high-producer cells but not in the mice bearing tumors induced by any other C1300 sublines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, repeated administration of anti-IFN-y antibodies should indicate more clearly the contribution of IFN-y in tumor suppression and rejection. In addition, IFN-y might induce the expression of tumorassociated antigen(s) (43,44) as well as MHC class I antigens, although the precise nature of the C1300 cell antigen is not yet known. Actually, preliminary experiments indicated that augmented CTL activity specific for the C1300 cell line was induced in the mice immunized with the high-producer cells but not in the mice bearing tumors induced by any other C1300 sublines.…”
Section: Discussionmentioning
confidence: 99%
“…29 Trastuzumab was recently reported to induce transcriptional inhibition of HER2 expression in HER2-overexpressing breast cancer cells by engaging Fc receptor-expressing immune effector cells to stimulate IFNg secretion in the presence of PBMC through STAT1 activation. 30 Because IFNg is a potent cytokine that stimulates HLA-ABC expression by activating STAT1 signaling, 31 we decided to examine whether the presence of immune effector cells influences any effect of trastuzumab on HLA-ABC expression. We first cultured BT474, SKBR3, SUM190, MDA-MB-361, and HCC1954 cells for 48 h in the presence or absence of trastuzumab in culture medium.…”
Section: Trastuzumab Increases Hla-abc Expression In Her2-overexpressmentioning
confidence: 99%
“…[8][9][10] IFN-␥ can also enhance antigen presentation on tumor cells through increased MHC class I and II expression. [11][12][13] Furthermore, IFN-␥ has been noted to modulate tumor angiogenesis by inhibiting endothelial tube formation in vitro. 14 Recombinant IFN-␥ has been used extensively in clinical trials, 15,16 however, the high doses required to induce an antitumorigenic response resulted in severe systemic side-effects.…”
Section: Introductionmentioning
confidence: 99%